Effects of High Temperature and Drought Stress on the Expression of Gene Encoding Enzymes and the Activity of Key Enzymes Involved in Starch Biosynthesis in Wheat Grains - Lu, Hongfang; Hu, Yangyang; Wang, Chenyang; Liu, Weixing; Ma, Geng; Han, Qiaoxia; Ma, Dongyun (Frontiers in Plant Science, 2019)
High temperature (HT) and drought stress (DS) play negative roles in wheat growth, and is the most important factors that limit grain yield. Starch, the main component of the wheat endosperm, accounts for 65-75% of grain weight, and is significantly influenced by environmental factors. To understand the effects of post-anthesis HT and DS on starch biosynthesis, we performed a pot experiment using wheat cultivar ‘Zhengmai 366’ under field conditions combined with a climate-controlled greenhouse to simulate high temperature. There were two temperature regimes (optimum day/night temperatures of 25/15oC and high day/night temperatures of 32/22oC from 10 days after anthesis to maturity) accompanied by two water treatments (optimum of ~75% relative soil water content, and a drought stress of ~50% relative soil water content). Optimum temperature with optimum water treatment was the control (CK). We evaluated the expression patterns of 23 genes encoding six classes of enzymes involved in starch biosynthesis in wheat grains using real-time qPCR. HT, DS, and HT+DS treatments altered gene expression profiles. Compared to the CK, expression of 22 of the 23 genes was down regulated by HT, and only one gene (ISA2) was up-regulated by all three treatments. The expression of 17 genes was up-regulated, while six genes, including GBSSI, AGPS2, BEIII, PHOL, ISA1, and AGPL2, were down-regulated by DS. Eleven genes were down-regulated and 12 were up regulated by HT+DS. HT, DS, and HT+DS altered the timing of starch biosynthesis and also influenced the accumulation of soluble sugars and sucrose as well as amylose, amylopectin, and total starch, leading to reductions in the starch accumulation rate and content. We also found that starch biosynthesis in wheat endosperm is modified by changes in the activities of key enzymes involved in starch biosynthesis and their gene expression profiles. Our study provide further evidence about the effects of stress on starch biosynthesis in wheat, as well as a physiological understanding of the impact of post-anthesis heat and drought stress on starch accumulation and wheat grain yield.